Freedom of Contract Illusion in the Employment Agreement - Puteri, Dina Silvia; Syahwal (Universitas Airlangga, 2025)
The presence of freedom of contract presupposes that the parties to the agreement are free to choose the agreement’s terms, structure, participation, and several other freedoms. As a type of contractual relationship, employment contracts are thought to include some degree of contractual freedom. This study attempts to answer the claim that employment contracts include freedom of contract by addressing the question of whether such a claim is supported by the premise of such freedom. The questions highlighted in this article will be investigated by reviewing the rules and legislation pertaining to employment contracts under Indonesian labor law, within the theoretical framework of critical realism. Critical realism provides a lens through which the underlying structures, mechanisms, and social conditions shaping employment relations can be uncovered, even when these are not directly observable. It allows researchers to move beyond surface-level legal formalities and examine the real constraints that limit workers’ choices and autonomy. Through this approach, the legal and social dimensions of employment contracts are assessed not only as written agreements but also as instruments shaped by power relations and economic dependence. According to research, employment contracts lack the justification of true contractual freedom. In practice, workers are not given the freedom to plan, decide, and select choices according to their preferences. Because of the employment contract, the worker becomes a party who is dependent on the employer, both personally and financially, particularly in terms of the wages determined and provided by the employer.